Disturbances in the Mechanism of Apoptosis as One of the Causes of the Development of Cancer Diseases - Paweł Rusin; Karolina Jabłońska (Studia Ecologiae et Bioethicae)
Apoptosis is a genetically programmed process that affects all multicellular organisms. This mechanism of programmed cell death is designed to protect the body against uncontrolled proliferation of cells with impaired functions. Apoptosis can occur through two major pathways. The extrinsic, initiated by signals from the death receptor, and the intrinsic one, resulting from a change in the permeability of the external mitochondrial membrane due to stress factors promoting the initiation of programmed cell death. Apoptosis may be influenced by many factors that may lead to suppressing the initiation of apoptotic pathways, and the damaged cell will develop, divide, and over time transform into a cancerous cell. As a result, cancer cells will be resistant to the applied chemo- and radiotherapy. The mechanisms responsible for apoptosis regulation are impaired, what eliminates the effects of therapies aimed at initiating this type of cell death. New types of molecular therapies provide an opportunity to increase the effectiveness of anticancer treatment, aiming at deficient proteins and suppressing or eliminating their antiapoptotic effects.